Faktor-Faktor yang Berhubungan dengan Kelelahan Mata pada Mahasiswa Universitas Negeri Semarang - Laura Marulia Subroto (Jurnal Anestesi, 2024)
According to Asosiasi Pengguna Jasa Internet Indonesia (APJII) in 2018, around 49.52% of all internet users in Indonesia are between 19 and 34 years old. The majority of this group are university students. The purpose of this study was to determine the factors associated with eyestrain in Universitas Negeri semarang students. This research is a quantitative research with cross sectional study design. The population of this study were students of Universitas Negeri Semarang in 2024 with a sample size of 125 people. This research was conducted in April-June 2024. The instrument used in this study was an online questionnaire in the form of Google Forms. The research analysis technique used the Spearman Rank test with SPSS. The results showed 108 students out of 125 students experienced eye fatigue (86.4%). The variables associated with this study were gender (p-value 0.047) and use of glasses (p-value 0.009), The study concluded that gender and use of glasses were associated with eyestrain.